Sudden, Painless Incontinence following Extracorporeal Shock Wave Lithotripsy: A Case Report. (30th September 2013) - Akbulut, Fatih; Akbas, Alpaslan; Sahin, Dilek
Abstract : Urinary incontinence is a stent-related complication; however, total incontinence is not often seen in emergency departments. We report a patient who presented with a sudden, painless, and total urinary incontinence after extracorporeal shock wave lithotripsy. This is the first case of total incontinence due to migrated ureteral double J stent through the external urethral sphincter into the urethra following extracorporeal shock wave lithotripsy.